The Effect of Participation in Internship Programs Certified and Project-Based Training on The Work Readiness of Students of SMK Prapanca 2 Surabaya - Fransiska Santri; Achmad Sholihin (Economics and Digital Business Review, 2026)
The purpose of this “study was to determine the readiness of third-grade students of SMK Prapanca 2 Surabaya to enter the workforce after participating in a certified internship program and project-based training. This study used a survey method with a quantitative approach. The sampling method used was purposive sampling, and the study population consisted of students of SMK Prapanca 2 Surabaya. Respondents were given a questionnaire to complete to collect data. Participation in the certified internship program and project-based training was the independent factor in this study, while students' work readiness was the dependent variable. Using the SPSS program, multiple linear regression analysis was used as the data analysis method. The results showed that students' work readiness was positively and significantly influenced by their involvement in the certified internship program. In addition, project-based training significantly improved students' readiness to enter the workforce. At SMK Prapanca 2 Surabaya, involvement in the certified internship program, training, and project-based training significantly improved students' readiness to enter the workforce.” It is hoped that this study will serve as an assessment tool for schools seeking to improve the quality of practice-based learning initiatives to better prepare students for the workforce.